Navigating higher education with chronic illness: analysing the interplay of personal traits, environmental influences, type 1 diabetes management, and quality of life - Ekaterina Malova (International Journal of Adolescence and Youth)
This study examines the influence of personal, behavioural, and environmental factors on diabetes management and diabetes-specific quality of life among college students with Type 1 Diabetes (T1D), guided by Social Cognitive Theory (SCT). Using multivariate analyses, the findings reveal that organizational support structures, such as the Office of Disability Services (ODS) and the College Diabetes Network (CDN), significantly enhance diabetes management and diabetes-specific quality of life, primarily through the mediating role of social support. Outcome expectations were positively associated with diabetes-specific quality of life, while the built environment facilitated diabetes self-management. Results underscore the importance of integrating campus infrastructure, formal support systems, and targeted strategies to enhance personal factors into interventions aimed at improving health outcomes for college students with T1D.